2019
DOI: 10.15171/ipp.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

Administration of vitamin D to ameliorate dyspnea of chronic obstructive pulmonary disease patients: a randomized controlled trial

Abstract: Introduction: As one of the most common causes of human morbidity and mortality, chronic obstructive pulmonary disease (COPD) affects millions around the world. Some evidences have already considered about association between serum levels of vitamin D and COPD. Objectives: This study was aimed to evaluate the effects of vitamin D supplementation on COPD improvement. Patients and Methods: This study was designed as a randomized controlled trial. Forty COPD patients with vitamin D deficiency were enrolled int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…3.4.5. Compound Nutrients FEV1 and FEV1/FVC% Eight studies were found involving the effects of complex nutritional supplements on lung function in patients, but the number of meta-analysis results was inconsistent due to data issues [52][53][54][55][57][58][59][60], and only seven of these articles were analyzed. The results proved that FEV1 was significantly increased in COPD patients after receiving multinutrient supplementation (WMD de : 8.38, 95% CI: 1.89, 14.87, p < 0.05; WMD af : 7.07, 95% CI: −0.34, 14.48, p < 0.05, Figure 4A,B).…”
Section: Magnesiummentioning
confidence: 99%
“…3.4.5. Compound Nutrients FEV1 and FEV1/FVC% Eight studies were found involving the effects of complex nutritional supplements on lung function in patients, but the number of meta-analysis results was inconsistent due to data issues [52][53][54][55][57][58][59][60], and only seven of these articles were analyzed. The results proved that FEV1 was significantly increased in COPD patients after receiving multinutrient supplementation (WMD de : 8.38, 95% CI: 1.89, 14.87, p < 0.05; WMD af : 7.07, 95% CI: −0.34, 14.48, p < 0.05, Figure 4A,B).…”
Section: Magnesiummentioning
confidence: 99%
“…Dastan et al documented the effect of vitamin D supplements on inflammation resolution by measuring serum levels of inflammatory markers [ 43 ]. Ghodrati et al performed a clinical trial and found out the curative role of this vitamin in treating dyspnea in COPD patients [ 44 ]. Supplementation can seemingly reduce the progression and morbidity of chronic diseases by decreasing the number of free radicals with antioxidant enzymes, as observed in the latest randomized control trial performed in Bangladesh by Anjum et al [ 45 ].…”
Section: Reviewmentioning
confidence: 99%